1987
DOI: 10.1080/01688638708405061
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological deficits and real-world dysfunction in cerebral revascularization candidates

Abstract: An assessment strategy using multiple levels of observation permitted description of problems in everyday living experienced by cerebral revascularization candidates. We contrasted the neuropsychological deficits and real-world dysfunction displayed by candidates for cerebral revascularization with that manifested by patients with severe spinal complaints. Correlations between selected neuropsychological scores and life quality measures were modest. Prediction of real-world performance in individuals likely wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…An important issue often neglected in studies such as the present study is the clinical relevance of statistically significant changes in cognitive function. Studies have demonstrated a link between objective assessments of cognitive functioning and everyday performance Newnan et al, 1978;McSweeny et al, 1985;Baird et al, 1987), but little or no research has investigated change in objective cognitive test performance in relation to changes in daily functioning. It is hypothesized that changes in objective psychological testing need to be of relatively large magnitude before they become important at the clinical level.…”
Section: Discussionmentioning
confidence: 99%
“…An important issue often neglected in studies such as the present study is the clinical relevance of statistically significant changes in cognitive function. Studies have demonstrated a link between objective assessments of cognitive functioning and everyday performance Newnan et al, 1978;McSweeny et al, 1985;Baird et al, 1987), but little or no research has investigated change in objective cognitive test performance in relation to changes in daily functioning. It is hypothesized that changes in objective psychological testing need to be of relatively large magnitude before they become important at the clinical level.…”
Section: Discussionmentioning
confidence: 99%
“…In order to be included in the study, subjects had to meet the following criteria: 1) the patient had to meet diagnostic criteria for dementia; (2) the patient had to be compliant with administration of a full neuropsychological evaluation; and (3) a reliable informant with whom the patient had frequent contact had to be present at the time of the appointment. Their mean Mattis Dementia Rating Scale (DRS) score was ‫5.21ע5.311‬ (range: 87-132), and their mean Mini-Mental State Exam (MMSE) score was ‫0.4ע0.22‬ (range: [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Patients' diagnoses included probable Alzheimer's disease (AD; n‫,)02ס‬ vascular dementia (n‫,)3ס‬ Lewy body disease (n‫,)2ס‬ alcohol dementia (n‫,)1ס‬ dementia due to multiple etiologies (n‫,)2ס‬ and dementia of unknown etiology (n‫.…”
Section: Participantsmentioning
confidence: 99%
“…Baird and coworkers studied 95 cerebral revascularization candidates and found a modest correlation between neurocognitive deficits and real-world dysfunction. 21 The EC-IC Bypass Study did not report improvement in cognitive function as a secondary outcome. 1 The COSS, in addition to determining whether stroke and death are reduced after bypass, will also assess clinical outcome using Rankin Scale Score, NIH-SS score, modified BI, and SS-QOL Assessment.…”
Section: Neurocognitive Follow-upmentioning
confidence: 97%